Pengaruh Model Pembelajaran Problem Based Instruction (PBI) terhadap Pengetahuan dan Sikap Remaja tentang HIV/AIDS di SMP Achmad Jani Puger Kabupaten Jember (The Effect of Model Learning: Problem Based Instruction (PBI) towards Knowledge and Attitude of - Dicky Andriansyah; Rondhianto Rondhianto; Ahmad Rifai (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
AIDS remains ranked as the third most deadly disease in Indonesia. The disease is caused by the HIV that can lead to lower a person's immune status to trigger an opportunistic infections and cause of death. The incidence of HIV disease in 2014 has reached 32,711 cases, at the age of 14-19 years of 1,717 cases (5.24%). Lack of knowledge among teenagers about HIV/AIDS makes their behavior leads to negative interactions or risk to free sex, misuse of syringes, and other related problems. Problem-based instruction (PBI) as a learning model is expected to change knowledge and attitudes of teenagers on HIV / AIDS. The results of dependent t-test t value -3.8380 for knowledge, and the value of t -22.174 for attitudes which means an increase in value after a given model of PBI with a mean difference -6.800 and -24.000 respectively for knowledge and attitudes. The p value 0.000 for the results obtained knowledge and attitudes.The p value was